Assessment of palatal bone thickness in adults with cone beam computerised tomography - Gracco Antonio; Luca Lombardo; Cozzani Mauro; Siciliani Giuseppe (Sciendo, 2023)
To determine the most suitable region of the palate for the insertion of miniscrews.